Transition metal-based materials and their catalytic influence on MgH2 hydrogen storage: A review - Oluwashina Philips Gbenebor; Abimbola Patricia Idowu Popoola (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
The dependence on fossil fuels for energy has culminated in its gradual depletion and this has generated the need to seek alternative source that will be environmentally friendly and sustainable. Hydrogen stands to be promising in this regard as energy carrier which has been proven to be efficient. Magnesium hydride (MgH2) can be used in storing hydrogen because of its availability, light weight and low cost. In this review, monoatomic, alloy, intermetallic and composite forms of Ti, Ni, V, Mo, Fe, Cr, Co, Zr and Nb as additives on MgH2 are discussed. Through ball milling, additive reacts with MgH2 to form compounds including TiH2, Mg2Ni, Mg2NiH4, V2O, VH2, MoSe, Mg2FeH6, NbH and Nb2O5which remain stable after certain de/hydrogenation cycles. Some monoatomic transition metals remain unreacted even after de/hydrogenation cycles. These formed compounds, including stable monoatomic transition metals, impart their catalytic effects by creating diffusion channels for hydrogen via weakening Mg - H bond strength. This reduces hydrogen de/sorption temperatures, activation energies and in turn, hastens hydrogen desorption kinetics of MgH2. Hydrogen storage output of MgH2/transition metal-based materials depend on additive type, ratio of MgH2/additive, ball milling time, ball –to combining materials ratio and de/hydrogenation cycle. There is a need for more investigations to be carried out on nanostructured binary and ternary transition metal-based materials as additives to enhance the hydrogen storage performance of MgH2. In addition, the already established compounds (listed above) formed after ball milling or dehydrogenation can be processed and directly doped into MgH2.